Care of women with female genital mutilation/cutting (Swiss Medical Weekly, 2011)
In multi-ethnic European society medical professionals are faced with an increasing number of women originating from countries where female genital mutilations/cuttings (FGM/C) are practised. Recent studies, however, emphasise the lack of knowledge on this subject. This review article aims to present FGM/C as a complex socio-healthcare and multidisciplinary issue, outlining the definition, classification, epidemiology and anthropologico-legal aspects of FGM/C. It explains the approach to be adopted to FGM/C women, focusing on defibulation, clitoral restoration/repair and re-infibulation. Finally, it reports on the discussions surrounding pricking/nicking and the proposals for alternative rituals in recent years.